Kandungan Gizi serta Sensori Nugget Ikan Patin dengan Penambahan Tempe Sebagai Alternatif Makanan Tambahan Balita dalam Upaya Pencegahan Stunting - Atasasih, Hesti; Paramita, Irma Susan; Rahayu, Dewi (Jurnal Kesehatan Komunitas, 2023)
Malnutrition in toddlers can result in growth disturbances, development, and low-quality human resources. Indonesia ranks fifth in the prevalence of stunting in the world. SSGI data for 2021 the prevalence of stunting in the city of Pekanbaru is 11.4%. The highest prevalence of stunting under five cases was found in the Lima Puluh District at 7.29%. The Supplemental Feeding Program (PMT) is one of the efforts to overcome and prevent stunting, the type of food ingredients used as PMT can be local food ingredients, namely catfish, in Riau the commodity of catfish is higher than other fish. Indonesia is the largest soybean market in Asia with the largest tempe production in the world. The study aimed to determine the nutritional and sensory content of catfish meat nuggets added with tempeh, which can be used as a solution for providing additional food for toddlers to prevent stunting. the research used in this study was experimental with a completely randomized design (CRD). The stages of this research consisted of, 2 namely the preliminary research stage to analyze the addition of the amount of tempeh in each treatment and further research namely the implementation of sensory tests and proximate analysis. The results of the study found that the most preferred treatment was the addition of 70% tempeh both from the attributes of color, aroma, taste, and texture. The ingredients contained in the nuggets are carbohydrates at 22.2%, protein at 4.9%, fat at 10.7%, fiber at 5.5%, ash content 0.1%, and water content 52.8%. Fish nuggets based on SNI contain 5.0% protein, 15.0% fat, 2.5% ash content, and 60% moisture content.